Mid Latitude Sporadic E-layer Variability during Ascending Phase of Solar Cycle 24 - Atulkar, R.; Khan, P. A.; Mansoori, A. A.; Purohit, P. K. (Journal of Scientific Research, 2017)
The paper presents a comparative study of the ionospheric sporadic E layer parameters (fbEs, foEs, and hEs) retrieved from ground based ionosonde at mid latitude station Yamagawa, Japan (31.20 N, 130.370 E) during the ascending phase of 24th solar cycle i.e. during January 2012 to December 2014. The comparison between the E-region parameters has been carried out on a diurnal, seasonal, annual and day night basis. The diurnal maxima of foEs, fbEs, and hEs are generally higher during high solar activity. From the present study it is found that the highest values of fbEs are observed during the summer while the lowest values are observed during autumn at mid latitude. Similarly, the highest values of foEs are observed during the summer season while the lowest values are recorded in autumn season. However, the highest values of hEs are recorded during the spring and the lowest values are recorded in autumn. The variability of Es during the day and night time is also studied. The sporadic E can form and disappear in a short time during either the day or night. We have also studied the percentage occurrence of sporadic E. The occurrence of Es changes from year to year.